Navigating New Terrain: Data Analytics In Auditing - Lim Wan Leng; Lai Siew Fong; Nor Haliza Che Hussain; Chin Wai Yin; Hen Kai Wah (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
The increasingly flexible working environment triggered by the pandemic pushed audit firms into rethinking how auditing should revolve around new technologies. Addressing operational sustainability and resilience became increasingly crucial in this age of disruption. As more and more businesses use big data and data analytics tools to enhance efficiency and effectiveness, applying data analytics in auditing can focus attention and resources to better manage risks. According to the global survey conducted by the International Federation of Accountants in 2018, Small and Medium Practices (SMP) in Malaysia generated 42% of revenues from auditing and assurance services. However, more than one-third of the SMPs in Malaysia stated zero technology development, which implied that the SMPs have either not utilized technology-enabled data analytics or have limited application of data analytics in their auditing practices. This study intends to explore the current practices in applying data analytics in auditing, its opportunities and challenges, especially in the Malaysian context. Questionnaire surveys will be distributed to gauge the current understanding of data analytics among audit firms registered with the Malaysian Institute of Accountants and to solicit responses on the perceived opportunities and challenges in adopting data analytics in auditing. The findings of this study could provide a glimpse of how auditors could effectively create value with the applications of technologies and navigate businesses in this new normal era. By embracing change, auditors could transform disruptions into opportunities for firms to recalibrate for a better future.